1989
DOI: 10.1038/ki.1989.250
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of hemodialysis fistula thrombosis. Early detection of venous stenoses

Abstract: Venous dialysis pressures were measured consecutively in 168 chronic hemodialysis patients for 265 patient-years of monitored dialysis. Venous dialysis pressure greater than 150 mm Hg measured by the protocol were considered elevated. Seventy-three patients had elevated venous dialysis pressures and 58 agreed to undergo elective venography (fistulogram). Fifty of 58 patients studied (86%) had significant venous stenoses. A combination of percutaneous transluminal angioplasty (PTA) and surgical revision were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
218
4
17

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 392 publications
(245 citation statements)
references
References 10 publications
6
218
4
17
Order By: Relevance
“…When the stenosis is not detected and corrected in a timely manner, grafts typically clot and require thrombectomy to restore their patency. A number of studies have found that an ongoing surveillance program for graft stenosis and timely intervention with angioplasty or surgical revision can substantially reduce (but not eliminate) the frequency of graft thrombosis (13,(23)(24)(25)(26). In the present study, thigh grafts tended to have less frequent angioplasties and more frequent thrombectomies than did upper extremity grafts (Table 3).…”
Section: Discussionmentioning
confidence: 43%
“…When the stenosis is not detected and corrected in a timely manner, grafts typically clot and require thrombectomy to restore their patency. A number of studies have found that an ongoing surveillance program for graft stenosis and timely intervention with angioplasty or surgical revision can substantially reduce (but not eliminate) the frequency of graft thrombosis (13,(23)(24)(25)(26). In the present study, thigh grafts tended to have less frequent angioplasties and more frequent thrombectomies than did upper extremity grafts (Table 3).…”
Section: Discussionmentioning
confidence: 43%
“…The in vitro study showed that the graft and the vein exhibit turbulent flow, whereas the artery may exhibit laminar entry flow or turbulent flow, depending on the Reynolds number: Re ϭ Q/15D ( is blood density in g/cm 3 , Q is in ml/min, and D is diameter in cm) (16). We found that as Re increased above 1500 in the artery, flow became turbulent (17).…”
Section: ϫ4mentioning
confidence: 84%
“…This preference is based on the assumption that progressive stenosis causes a gradual reduction in Q that leads to stasis and thrombosis (2). Landmark nonrandomized studies reported that surveillance of function improves graft outcomes (3,4), but more recent randomized controlled trials have not confirmed this (5-7). Moreover, monthly Q measurements have proved to be an inaccurate predictor of thrombosis (8 -11).…”
mentioning
confidence: 99%
“…26,33 Approximately 80% of thrombotic events are related to venous stasis produced by stenotic lesions. 38 Excessive vessel compression after needle withdrawal, to avoid bleeding, and intradialytic and post-dialytic hypotensive episodes, which are frequent in children, are also important causes of thrombosis. 39 Although not computed in this study, our long experience in HD pediatric units has shown that hypotension is frequent during HD sessions, chiefly with inadequate ultrafiltration calculation or removal of too much water too fast.…”
Section: Discussionmentioning
confidence: 99%